Development of Tribal Marketing in Postmodern Society - Rakšnys, Adomas Vincas; Žilinskienė, Deimantė (Socialiniai tyrimai, 2021)
Relevance and problem of the topic. Global product and service innovations are driving changes in consumer behavior. Business organizations try to apply a variety of marketing strategies to take into account changing consumer values and behaviors, to form new relationships and emotional experiences for their clientele (Cova, Dalli, 2009, p. 315; Sanz-Marcos, 2020, p. 473). Retrospectively, modernized society was dominated by developed and stable social structures and hierarchies, while postmodern society was dominated by social networks of micro-groups, in which individuals establish strong emotional connections and attitudes toward life. In order to ensure effective attraction of new customers and loyalty of existing customers in a postmodern society, business organizations should take into account and acess cultural change, societal fragmentation, and declining social connections. Renewing these social connections in the form of a consumer tribe in connection with the consumption of a product or service is a marketing opportunity and necessity. The concept of tribal marketing in the context of marketing application is related to the recurring quasi-archaic values of consumers: group identity, religiosity, syncretism, group narcissism (Necualaesei, 2017, pp. 122–125; Pinto de Lima, Brito, 2012, p. 293; Cova, Cova, 2002, p. 4). The reintegration of these values in the new conditions is extremely important, especially emphasizing the long-term tendencies of social rationalization of society in many spheres of life, the importance of qualitative indicators in the modernist period. In postmodern society, there is a growing impulse to distance oneself from rational forms of life and return to a natural or primitive state, and this need can be exploited through tribal marketing, when analyzing tribal communities in surfing, where marketing ideals become freedom, simplicity, escape from everyday life and strong impressions. (Canniford, Shankar, 2011, p. 35–46). Other significant tribes such as the Goths, (Cova, Dalli, 2009, p. 323), Harley-Davidson motorcyclists, pipe collectors, and smokers can also be mentioned (Pace et al., 2011, pp. 314-320). V. Badrinarayanan, et. al., is of the opinion that communities of various online games can also be assigned to tribes (Barnes and Mattsson, 2016, p. 98). The problem analyzed in this article can be defined by the following questions: What promotes the formation of tribal marketing and what are the specifics of its application? What are the differences between tribal marketing and traditional marketing? How virtual tribe could formed? The object of the article is the development of tribal marketing and application possibilities The aim of the article is to find out the development and application possibilities of tribal marketing in the postmodern society. Tasks: 1) to theoretically define the concept and essential principles of tribal marketing; 2) to reveal the cultural origins of tribal marketing and the reasons for its formation; 3) to identify the essential differences of tribal marketing in comparison with traditional marketing tools; 4) to reveal the changes related to the transition to the formation of virtual tribes. Methods: methods of analysis, synthesis, generalization and comparative analysis of scientific literature. An analysis of the scientific literature has revealed that tribal marketing is a theory that focuses on specific subcultures, and specific products or services become cult objects and emblems that represent belonging to these subcultures, encouraging individual consumption behavior. Tribal subcultures are characterized by strong emotional ties and experiences, common interests, and specific activities. These individuals exist in a peculiar subculture characterized by peculiar myths, values, rituals, language, and hierarchy. It is important to understand that individuals can belong to several tribes at the same time, and tribes are not limited by physical boundaries. The cultural origins of tribal marketing are related to the fragmented and individualized state of postmodern society and the need to reconstruct social ties. In postmodern society, the reintegration of archaic relations takes place under new conditions. The structure of tribal marketing integrates cultural aspects, linking them with the sentiments of primitive society, nostalgia for naturalness, the need for a closer social relationship with the group. However, with the changing technological environment and socio - cultural changes, the formation of tribes is moving into a virtual space. Technological changes have led to the formation of virtual tribes. In a virtual space, individuals and their groups can share the same emotions, opinions, information about a brand, product, or service. Technological change has made it possible for individuals from all over the world to find a group or groups united by common cultural elements. The essential criteria of a virtual tribe are that the tribe has a collective consciousness, rituals and traditions, duties, a sense of commitment to both the whole tribal community and its members. When analyzing virtual tribes, it is useful to rely on the 8E model, as it covers a systematic perspective in assessing the structure and functioning of virtual tribes. The processes of creating new social connections and forms are intensified by modern technologies. Users can interact with each other, regardless of territorial barriers, share information, form virtual tribes (Pinto de Lima, Brito, 2012, pp. 291– 292). It is becoming more important for business organizations not only to take advantage of traditional tribal marketing opportunities, but also to adapt to the opportunities provided by virtual space. However, the topic of tribal marketing is poorly researched in Lithuania.